Epiphytic Plants: Perspective on Their Diversity, Distribution, Systematics and Conservation in the Changing Environment - Thorsten Krömer; Sven Peter Batke (Plants)
Epiphytic plants are vital components of tropical and subtropical forests, contributing significantly to biodiversity, ecosystem function, and structural complexity [...]